PENINGKATAN HASIL BELAJAR PKn DENGAN PENERAPAN KOOPERATIF MODEL GROUP INVESIGATION - Komaria, - (WAHANA PEDAGOGIKA, 2016)
This study aimed to determine the increase of learning motivation and learning outcomes on PKN at sixth graders after the applied of of cooperative models Group Invesigation (GI) methods. This study used the design of classroom action research (PTK) Kemmis and Taggart models with spiral from one cycle to the next. Each cycle included planning, action, observation, and reflection. The subjects were students of class VI at the first state Elementary School Tawangrejo Sub Turi Lamongan. The research instrument used was (1) the observation sheet of the studentsâ activities, (2) the observation sheet of teacherâs activity, and (3) a test sheet. Data were analyzed using simple statistics. The results showed that with the implementation of learning PKN group model of cooperative methods of investigation (GI) can increase the students motivation. This was evidenced from their improving of the studentsâ learning outcomes, it was the first cycle of absorption of students on average 64.00 into 81.00 in the second cycle. And the data completeness of classes were also increasing that was the first cycle to 70% increased to 90% in the second cycle.